Interobserver reliability of Feline Dermatitis Extent and Severity Index (FEDESI) and Scoring Feline Allergic Dermatitis (SCORFAD) and the relationship between lesion scores and pruritus. Issue 5 (2nd August 2021) - Brame, Bailey E.; Canning, Peter; Morris, Daniel O.; Drobatz, Kenneth J.; Rook, Kathryn; Cain, Christine L.
Abstract : Background: Feline Dermatitis Extent and Severity Index (FEDESI) and Scoring Feline Allergic Dermatitis (SCORFAD) are scales used to assess lesion severity in cats with allergic dermatitis. Interobserver reliability has not been assessed for either. Hypothesis and objectives: To determine interobserver reliability for FEDESI and SCORFAD, and the relationship between lesion scores and pruritus. Animals: Thirty‐eight cats presenting for pruritus. Methods and materials: Each cat's lesions were scored by two observers at each visit using both FEDESI and SCORFAD (n = 117 paired observations). Spearman's rho was calculated to assess correlation between scales and between each scale and the owner‐reported pruritus Visual Analog Scale (pVAS). Concordance correlation coefficients were calculated between observers for each scale, and Bland–Altman plots were used to visually represent the relationship between paired scores. Results: FEDESI and SCORFAD were strongly positively correlated with one another (rho = 0.84, P  < 0.001). Each scale showed fair correlation with pVAS (rho = 0.42, P  < 0.001; rho = 0.38, P  < 0.001, respectively). There was good concordance between observers for both scales, with a correlation coefficient of 0.77 for FEDESI and 0.80 for SCORFAD [intraclass correlation coefficient (ICC) 95%, confidence interval (CI) 0.69–0.83; ICC 95%, CI 0.72–0.86, respectively]. Median lesion score was low (FEDESI 20; SCORFAD 4), which may improve interobserver reliability. Conclusions and clinical importance: There is good interobserver reliability for both FEDESI and SCORFAD. FEDESI and SCORFAD are positively correlated with one another and with pVAS. These findings support use of both scales in clinical research and assessment. Abstract : Background – Feline Dermatitis Extent and Severity Index (FEDESI) and Scoring Feline Allergic Dermatitis (SCORFAD) are scales used to assess lesion severity in cats with allergic dermatitis. Interobserver reliability has not been assessed for either. Hypothesis and objectives – To determine interobserver reliability for FEDESI and SCORFAD, and the relationship between lesion scores and pruritus. Conclusions and clinical importance – There is good interobserver reliability for both FEDESI and SCORFAD. FEDESI and SCORFAD are positively correlated with one another and with pVAS. These findings support use of both scales in clinical research and assessment. RÉSUMÉ: Contexte: Le FEDESI (Feline Dermatitis Extent and Severity Index) et le SCORFAD (Scoring Feline Allergic Dermatitis) sont des échelles utilisées pour déterminer la sévérité des lésions chez les chats atteints de dermatite allergique. La fiabilité interobservateur n'a pas été déterminée. Hypothèses/Objectifs: Déterminer la fiabilité interobservateur pour FEDESI et SCORFAD et la relation entres les scores lésionnels et le prurit. Sujets: Trente huit chats présentés pour prurit. Matériels et méthodes: Chaque lésion a été scorée par deux investigateurs à chaque visite à l'aide du FEDESI et du SCORFAD (n = 117 observations pairées). Le rho de Spearman a été calculé pour déterminer la corrélation entre les échelles et entre chaque échelle et le pVAS (pruritus Visual Analog Scale) rapporté par les propriétaires. Les coefficients de corrélation de concordance ont été calculés entre les investigateurs pour chaque échelle et les plots de Bland‐Altman ont été utilisés pour représenter visuellement les relations entres les scores pairés. Résultats: Les FEDESI et SCORFAD ont été fortement corrélés entre eux (rho = 0.84, P  < 0.001). Chaque échelle a montré une bonne corrélation avec pVAS (rho = 0.42, P  < 0.001; rho = 0.38, P  < 0.001, respectivement). Il y avait une bonne concordance entre les investigateurs pour les deux échelles, avec un coefficient de corrélation de 0.77 pour FEDESI et 0.80 pour SCORFAD [coefficient de corrélation intraclasse (ICC) 95%, intervalle de confiance (CI) 0.69–0.83; ICC 95%, CI 0.72–0.86, respectivement]. Le score de lésion médian était faible (FEDESI 20; SCORFAD 4), ce qui pourrait améliorer la fiabilité interobservateur. Conclusions et importance clinique: Il y avait une bonne fiabilité interobservateur pour le FEDESI et pour le SCORFAD ; les deux étaient positivement corrélés entre eux et avec la pVAS. Ces données supportent l'utilisation des deux échelles dans la recherche et la détermination des recherches cliniques. Resumen: Introducción: el índice de extensión y gravedad de la dermatitis felina (FEDESI) y la valoración de la dermatitis alérgica felina (SCORFAD) son escalas que se utilizan para evaluar la gravedad de las lesiones en gatos con dermatitis alérgica. La fiabilidad interobservador no ha sido evaluada para ninguna. Hipótesis y objetivos: Determinar la fiabilidad interobservador de FEDESI y SCORFAD, y la relación entre las valoraciones de las lesiones y el prurito. Animales: Treinta y ocho gatos que se presentaron por prurito. Métodos y materiales: dos observadores calificaron las lesiones de cada gato en cada visita utilizando tanto FEDESI como SCORFAD (n = 117 observaciones pareadas). Se calculó la rho de Spearman para evaluar la correlación entre las escalas y entre cada escala y la escala análoga visual de prurito indicada por el propietario (pVAS). Se calcularon los coeficientes de correlación de concordancia entre los observadores para cada escala, y se utilizaron gráficos de Bland‐Altman para representar visualmente la relación entre las valoraciones pareadas. Resultados: FEDESI y SCORFAD se correlacionaron de forma muy positiva entre sí (rho = 0, 84, P <0, 001). Cada escala mostró una correlación justa con pVAS (rho = 0, 42, P <0, 001; rho = 0, 38, P <0.001, respectivamente). Hubo buena concordancia entre los observadores para ambas escalas, con un coeficiente de correlación de 0, 77 para FEDESI y 0, 80 para SCORFAD [coeficiente de correlación intraclase (ICC) 95%, intervalo de confianza (IC) 0, 69‐0, 83; ICC 95%, IC 0, 72‐0, 86, respectivamente]. La puntuación media de las lesiones fue baja (FEDESI 20; SCORFAD 4), lo que puede mejorar la fiabilidad interobservador. Conclusiones e importancia clínica: existe una buena fiabilidad interobservador tanto para FEDESI como para SCORFAD. FEDESI y SCORFAD se correlacionan positivamente entre sí y con pVAS. Estos hallazgos apoyan el uso de ambas escalas en la investigación y evaluación clínicas. Zusammenfassung: Hintergrund: Der Feline Dermatitis Extent and Severity Index (FEDESI) und die Scoring Feline Allergic Dermatitis (SCORFAD) sind Werteskalen, die verwendet werden, um den Schweregrad der Veränderungen bei Katzen mit allergischer Dermatitis zu erfassen. Für beides wurde bisher keine Verlässlichkeit zwischen den BeobachterInnen erfasst. Hypothese und Ziele: Eine Bestimmung der Verlässlichkeit zwischen den BeobachterInnen für FEDESI und SCORFAD, sowie des Zusammenhangs zwischen Ausmaß der Veränderungen und dem Juckreiz. Tiere: Achtunddreißig Katzen, die wegen Juckreiz vorgestellt wurden. Methoden und Materialien: Die Veränderungen einer jeden Katze wurden von zwei BeobachterInnen bei jedem Besuch mittels FEDESI und auch SCORFAD bewertet (n = 117 gepaarte Beobachtungen). Spearman´s Rho wurde kalkuliert, um den Zusammenhang zwischen den Bewertungsskalen und zwischen einer jeden Skala und der von den BesitzerInnen beschriebenen Visual Analog Scale (pVAS) zu erfassen. Konkordanz Korrelationskoeffizienten wurden zwischen den BeobachterInnen für jede Skala kalkuliert und Bland‐Altman Plots wurden angewendet, um den Zusammenhang zwischen den gepaarten Skalen visuell zu zeigen. Ergebnisse: FEDESI und SCORFAD zeigten eine stark positive Korrelation (rho = 0, 84, P < 0, 001). Jede Skala zeigte eine mäßige Korrelation mit pVAS (rho = 0, 42, P < 0, 001 bzw rho = 0, 38, P < 0, 001). Es bestand eine gute Konkordanz zwischen den BeobachterInnen bei beiden Skalen, wobei der Korrelationskoeffizient bei 0, 77 für FEDESI und bei 0, 80 für SCORFAD lag [Intraclass Korrelationskoeffizient (ICC) 95%, Konfidenzintervall (CI) 0, 69‐0, 38 bzw ICC 95%, CI 0, 72‐0, 86%]. Die medianen Werte der Veränderungen waren niedrig (FEDESI 20; SCORFAD 4), was die Verlässlichkeit zwischen den BeobachterInnen verbessern könnte. Schlussfolgerungen und klinische Bedeutung: Es besteht eine gute Verlässlichkeit zwischen den BeobachterInnen sowohl für FEDESI wie auch für SCORFAD. FEDESI und SCORFAD zeigen miteinander und mit pVAS eine positive Korrelation. Diese Ergebnisse unterstützen den Einsatz beider Skalen in der klinischen Forschung und Beurteilung. 要約: 背景: 猫の皮膚炎の程度と重症度指数 (FEDESI) および猫のアレルギー性皮膚炎のスコアリング (SCORFAD) は、アレルギー性皮膚炎の猫の病変の重症度を評価するために用いられる尺度である。いずれも観察者間の信頼性も評価されていない。 仮説と目的: 本研究の目的は、FEDESIおよびSCORFADの観察者間信頼性、病変スコアおよび痒みの関係を明らかにすることであった。 供試動物: 掻痒のある38頭の猫。 材料と方法: 各猫の病変を、FEDESIおよびSCORFADの両方を使用して各診察時に2人の観察者がスコアリングした (n = 117ペアの観察) 。Spearman's rhoは、スケール間および各スケールと飼い主が報告したそう痒の視覚的アナログスケール (pVAS) との相関関係を評価するために計算された。一致性相関係数は、各スケールの観察者間で計算され、ブランド‐アルトマンプロットは、ペアのスコア間の関係を視覚的に表すために使用された。 結果: FEDESIおよびSCORFADは、互いに強く正の相関を示した (rho = 0.84、P <0.001) 。各スケールは、pVASとの公正な相関を示した (それぞれ rho = 0.42、P <0.001; rho = 0.38、P <0.001) 。両尺度ともに観察者間の一致は良好で、FEDESIの相関係数は0.77、SCORFADの相関係数は0.80であった[クラス内相関係数 (ICC)95%、信頼区間 (CI) 0.69–0.83; ICC 95% 、CI 0.72〜0.86、それぞれ]。病変スコアの中央値は低く (FEDESI 20; SCORFAD 4) 、これは観察者間の信頼性を向上させる可能性がある。 結論と臨床的重要性: FEDESIおよびSCORFADの両方に優れた観察者間信頼性がある。 FEDESIおよびSCORFADは、相互に、そしてpVASと正の相関を示した。これらの調査結果は、臨床研究や評価における両スケールの使用を支持するものである。 摘要: 背景: 猫皮炎程度和严重程度指数(FEDESI)和猫过敏性皮炎评分(SCORFAD)是用于评估过敏性皮炎猫病变严重程度的量表。尚未评估观察者间的可靠性。 假设和目的: 确定FEDESI和SCORFAD的观察者间可靠性, 以及病变评分和瘙痒之间的关系。 动物: 38只猫出现瘙痒。 方法和材料: 两名观察者在每次访视时, 使用FEDESI和SCORFAD对每只猫的病变进行评分 (n = 117对观察结果) 。计算Spearman rho, 评估量表之间以及每个量表与宠主报告的瘙痒视觉模拟量表(pVAS)之间的相关性。计算各量表观察者间的一致性相关系数, 采用Bland—Altman图直观代表配对评分之间的关系。 结果: FEDESI和SCORFAD彼此之间呈强正相关 (rho = 0.84, P < 0.001)。每个量表均显示与pVAS一般相关 (分别为rho = 0.42, P < 0.001; rho = 0.38, P < 0.001) 。两种量表观察者之间具有良好的一致性, FEDESI的相关系数为0.77, SCORFAD的相关系数为0.80[组内相关系数(ICC)95%, 置信区间(CI) 0.69‐0.83; ICC 95%, CI 0.72‐0.86]。中位病变评分较低(FEDESI 20;SCORFAD 4), 可改善观察者间可靠性。 结论和临床重要性: FEDESI和SCORFAD具有良好的观察者间可靠性。FEDESI和SCORFAD相互呈正相关, 与pVAS呈正相关。这些发现支持在临床研究和评估中使用这两种量表。 Resumo: Contexto: A Feline Dermatitis Extent and Severity Index (FEDESI) e a Scoring Feline Allergic Dermatitis (SCORFAD) são escalas utilizadas para avaliar a gravidade das lesões em gatos com dermatite alérgica. A confiabilidade interobservador ainda não foi avaliada para ambas as escalas. Hipótese e objetivos: Determinar a confiabilidade interobservador para FEDESI e SCORFAD, e a relação entre escores de lesão e prurido. Animais: Trinta e oito gatos apresentando prurido. Métodos e materiais: As lesões de cada gato foram classificadas por dois observadores a cada visita utilizando ambos FEDESI e SCORFAD (n = 117 observações pareadas). Calculou‐se o rho de Spearman para avaliar a correlação entre as escalas e entre cada escala e o prurido relatado pelos proprietários na pruritus visual analogue scale (pVAS) . Os coeficientes de concordância de correlação foram calculados entre os observadores para cada escala, e gráficos de Bland‐Atman foram utilizados para representar visualmente a relação entre os escores pareados. Resultados: FEDESI e SCORFAD foram fortemente correlacionados positivamente entre si (rho = 0, 84, P  < 0, 001). Cada escala apresentou correlação moderada com o pVAS (rho = 0, 42, P  < 0, 001; rho = 0, 38, P  < 0, 001, respectivamente). Houve boa concordância entre os observadores para ambas as escalas, com um coeficiente de correlação de 0, 77 para FEDESI e 0, 80 para SCORFAD [coeficiente de correlação interclasse (ICC) 95%, intervalo de confiança (IC) 0, 69‐0, 83; ICC 95%, CI 0, 72‐0, 86, respectivamente]. O escore médio de lesão foi baixo (FEDESI 20; SCORFAD 4), o que deve contribuir para a melhora na confiabilidade interobservador. Conclusões e importância clínica: Há uma boa confiabilidade interobservador para ambos FEDESI e SCORFAD. FEDESI e SCORFAD são positivamente correlacionados entre si e com o pVAS. Estes achados corroboram com a utilização de ambas as escalas em avaliações clínicas e de pesquisas.